SOME CHARACTERIZATION FOR RECORD VALUES - Al-Shomrani, Ali A.; Shawky, A.I. (Acta Scientiae et Intellectus, 2024)
In this paper we discussed some explicit forms for conditional expectations of record values. We study the necessary and sufficient conditions such that the conditional expectations of record values hold for some distribution functions.